(untitled) (Збірник наукових праць Галузеве машинобудування будівництво, 2017)
The determining of reliability of water systems is introduced, is derived formulas for definition the reliability of some water pipe structures and is made the comparative analysis of reliability and topology of these structures. The engineering method of analysis the reliability of tracing the cyclical water pipe systems is developed, which is allowed to select a structure of network with maximum reliability, is defined the limit reliability of area of network, is identified that areas which would increase the reliability of the structure during its development. The method of graph–analytic formation of tracing the new circular water pipe system was developed ed, which would given the opportunity to build a number of competitive options for trace circular water network and choose the best for reliability. Keywords: the reliability of the network structure, the topology, the boundary reliability of sections.